Pengaruh Literasi Pajak Dan Digitalisasi Sistem Perpajakan Terhadap Niat Patuh Pajak Pada Generasi Z - Aurelia, Akilah; Yusuf, Muhammad; Julian, Alfito; Meidiana, Ghaida; Linawati, Linawati (Prisani Cendekia, 2025)
This study aims to analyze the influence of tax literacy and the digitalization of the tax system on tax compliance intention among young taxpayers. The transformation of the tax system toward digital-based services requires adequate tax knowledge as well as technological adaptability from taxpayers, particularly those who have grown up in a digital environment. This study employs a quantitative approach using a survey method through questionnaires distributed to young respondents registered as taxpayers. The data were analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The results indicate that tax literacy has a positive effect on taxpayers’ compliance intention. In addition, the digitalization of the tax system is proven to have a positive and more dominant influence in encouraging compliance intention. These findings suggest that the convenience, efficiency, and accessibility of digital tax services play an important role in shaping compliance attitudes among younger generations. This study provides implications for tax authorities in formulating compliance enhancement strategies through strengthening tax education and optimizing digital services.